2020
DOI: 10.26480/ecr.01.2021.08.10
|View full text |Cite
|
Sign up to set email alerts
|

The Initial Ion Effect of Heavy Metals Adsorption by Using Hydrothermal Carbonization Banana Peels

Abstract: Accumulation of heavy metals in water is of particularly important because it can impact upon human health through possible contamination of food. The use of banana peel was investigated. Hydrothermal carbonization (HTC) was chosen as alternative process. The objective of this project is to synthesize banana peel hydrochars adsorbent via HTC process and to evaluate the heavy metals adsorption performance of banana peel hydrochars adsorbent. Conventional methods in removal of heavy metals require high operation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Consequently, they have the capability to inhibit the particular biological activities of specific biomolecules like proteins and enzymes [7]. Continual release of these metals into the environment significantly impairs aquatic habitats [8], leading to their accumulation in crucial organs like the brain, muscles, kidneys, and liver, and ultimately causing various deadly illnesses and conditions, including hepatitis, renal disease, nervous system disorders, anemia, encephalopathy, or nephritis, and can result in death [9][10][11][12][13]. Moreover, their accumulation within living tissues has been linked to the development of numerous diseases, including cancer [14].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, they have the capability to inhibit the particular biological activities of specific biomolecules like proteins and enzymes [7]. Continual release of these metals into the environment significantly impairs aquatic habitats [8], leading to their accumulation in crucial organs like the brain, muscles, kidneys, and liver, and ultimately causing various deadly illnesses and conditions, including hepatitis, renal disease, nervous system disorders, anemia, encephalopathy, or nephritis, and can result in death [9][10][11][12][13]. Moreover, their accumulation within living tissues has been linked to the development of numerous diseases, including cancer [14].…”
Section: Introductionmentioning
confidence: 99%
“…To further evaluate adsorption kinetics parameters, the pseudo-first-order and pseudosecond-order models stated in Equations ( 9) and (10) were introduced [30,43].…”
Section: Inductively Coupled Plasma Mass Spectroscopy (Icp-ms) Analysesmentioning
confidence: 99%
“…For example, industrial wastewater contains different derivatives of heavy metals, for example, arsenic (As), chromium (Cr), cobalt (Co), nickel (Ni), copper (Cu), zinc (Zn), manganese (Mn), silver (Ag), cadmium (Cd), lead (Pb), mercury (Hg), and organic dyes, among others. These pollutants are continuously discharged into the ecosystem, can accumulate in muscles, brain, bones, liver, and kidney, and may cause many severe diseases and disorders including kidney failure, nervous illness, anemia, encephalopathy, hepatitis, nephritic syndrome, and even death [3,[6][7][8][9][10]. Furthermore, long-term exposure to arsenic via drinking water and contaminated foods has led to several lethal diseases, such as gangrene, keratosis, cancer, diabetes, and cardiovascular disorders, among others [2,11], while chromium is classified as a priority pollutant [12] and can be carcinogenic, toxic, and mutagenic to living organisms.…”
Section: Introductionmentioning
confidence: 99%
“…The main problems faced by banana peels are low recovery efficiency and long-term environmental pollution from landfilling. Studies have shown that the preparation of high-value hydrothermal carbon from banana peels using the hydrothermal method [ 17 ] exhibits good adsorption performance for lead and arsenic [ 16 , 18 , 19 ]. In a previous study, a batch experiment removed Pb(II) through a derived powered adsorbent from the banana peel.Parameters such as pH, dosage, time, and agitating speed were evaluated, and a maximum capacity of 2.18 mg/g was observed after adsorption [ 20 ].…”
Section: Introductionmentioning
confidence: 99%